2011
DOI: 10.1038/pj.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive disruption of ‘liquid marbles’ prepared from water and poly(6-(acrylamido) hexanoic acid)-grafted silica particles

Abstract: A chain transfer agent was immobilized onto the surface of 11-lm diameter silica particles (CPD-SiO 2 ) for use in reversible addition-fragmentation chain transfer (RAFT)-controlled radical polymerization. pH-responsive poly(6-(acrylamido)hexanoic acid) (PAaH)-grafted silica particles (PAaH-SiO 2 ) were prepared via RAFT-controlled radical polymerization using CPD-SiO 2 . Immobilization of the PAaH chains onto the surface of silica particles was confirmed by thermogravimetric analysis, attenuated total reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…The pH-responsive liquid marble disintegrates on addition of NaOH aqueous solution to the bulk aqueous phase because the particle surface becomes hydrophilic, owing to the ionization of the pendant hexanoic acid groups in the grafted polymer chains. 6,7 In this study, pH-responsive liquid marbles were prepared using a hydrophobic fluorinated powder, 2H,2H,3H,3H-heptadecafluoroundecanoic acid (HFUA). To prepare pH-responsive liquid marbles without much time and labor, we used HFUA as a pH-responsive powder (Figure 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The pH-responsive liquid marble disintegrates on addition of NaOH aqueous solution to the bulk aqueous phase because the particle surface becomes hydrophilic, owing to the ionization of the pendant hexanoic acid groups in the grafted polymer chains. 6,7 In this study, pH-responsive liquid marbles were prepared using a hydrophobic fluorinated powder, 2H,2H,3H,3H-heptadecafluoroundecanoic acid (HFUA). To prepare pH-responsive liquid marbles without much time and labor, we used HFUA as a pH-responsive powder (Figure 1).…”
mentioning
confidence: 99%
“…The liquid marble was floated on the bulk phase containing luminol and H 2 O 2 ( Figure 6 and Video S3). For the reaction, luminol was activated with H 2 O 2 , and K 3 [Fe(CN) 6 ] was the catalyst. When the liquid marble was broken by adding NaOH, the activated luminol came in contact with the K 3 [Fe(CN) 6 ] catalyst, causing it to exhibit luminescence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7 There have recently been reports of liquid marbles whose stability can be controlled by external stimuli; these are known as stimuli-responsive liquid marbles. Liquid marbles stabilized by particles containing pH-responsive polymers, such as deprotonated hydrophobic poly[2-(dimethylamino)ethyl methacrylate], 8 poly(2-vinylpyridine) (P2VP), 9 or protonated hydrophobic poly [6-(acrylamide)hexanoic acid], 10 which can float on the surface of bulk water, disintegrate upon addition of acid or base to the bulk water, because the particle surface becomes hydrophilic due to ionization of the pH-responsive polymers. Recently, Wang et al 11 reported the preparation of magnet-and UV-responsive liquid marbles using Fe 3 O 4 /SiO 2 particles with a pH-responsive block copolymer containing P2VP and a photo acid generator (PAG).…”
mentioning
confidence: 99%